Large systems of interacting particles and the porous medium equation - Oelschläger, Karl (Journal of differential equations, 2004)
We study the empirical processes of systems of interacting particles, whose time evolution is given by coupled ordinary differential equations. In particular, as the population size tends to infinity, we derive different versions of the porous medium equation as limit dynamics.